The Coupling of the Numerical Heat Transfer Model of the Pauzhetka Hydrothermal System (Kamchatka, USSR) with Hydroisotopic Data - Kiryukhin, A.V.; Sugrobov, V.M. (Institute of Volcanology, Petropavlovsk-Kamchatsky, 6830006, USSR, 1986)
The application of the two-dimensional numerical heat-transfer model to the Pauzhetka hydrothermal system allowed us to establish that: (1) a shallow magma body with the anomalous temperature of 700-1000 C and with a volume of 20-30 kmsup 3 may be a heat source for the formation of the Pauzhetka hydrothermal system. (2) The water feeding source of the Pauzhetka hydrothermal system may be meteoric waters which are infiltrated at an average rate of 5-10 kg/s {center_dot} kmsup 2. The coupling of the numerical heat-transfer model with hydroisotopic data (D,T,sup 18O) obtained from the results of testing of exploitation wells, rivers and springs is the basis to understand more clearly the position of recharge areas and the structure of water flows in the hydrothermal system.